Smart technologies as social innovation and complex social issues of the Z generation - Roblek, Vasja; Mesko, Maja; Dimovski, Vlado; Peterlin, Judita (Kybernetes, 2018)
This paper aims to present how contemporary students are self-organizing using smart technologies (ST) and the future social implications of ST. The research model is based on the concepts of the soft system methodology, social systems thinking, innovative smart systems, and cybernetic and knowledge management. Design/methodology/approach The study contains elements of exploratory and descriptive case studies. Narrative analysis and interpretation of the collected data have been carried out. Findings Students mostly use ST to save time when studying and in their free time. Students are surprised by how ST developed and are cautious when imagining how the technology will change and affect their lives. They are concerned regarding several ethical dilemmas of using it, such as privacy and spending time with their loved ones and friends. Students perceive their self-organization in the future as very dependent on the availability of ST in institutional settings (e.g. education and business process) as well as their personal lives. Students discuss their present perceptions about what the future will be and note that social system will be more dynamic in terms of socialization, and loss of personal contact with their friends and family is seen as the main threat. Research limitations/implications The research is qualitative, and the questionnaire was carried out among business students at the Faculty of Economics, University of Ljubljana, Slovenia. Practical implications The paper offers an understanding of the usage of ST among business students. This study provides a road map of a few possible ways for usage of ST among students. The topic is also relevant for human resource managers, technology developers and marketing strategists for their better understanding of the behaviour of young people using ST in professional or private environments. Social implications The findings can be useful for professors in identifying different learning methods that are useful for their students. Originality/value The authors offer conceptualizations of ST within the social innovation framework and provide a contemporary understanding young people’s ST usage.
N'AVONS PAS ACCÈS VERSION ORIGINALE. Version postprint sur ResearchGate
Keywords: Technologies intelligentes; Version libre-accès ResearchGate